Edukasi Fisioterapi Mengenai Neck Pain terhadap Postur Tubuh pada Pekerja UPTD Agribisnis Pontianak Utara - Anggriani, Devi; Bayu Prastowo (Health Care : Journal of Community Service, 2025)
Neck pain is a common health problem that often affects workers, especially those who engage in strenuous physical activity or have poor posture habits. Every job carries the risk of accidents or occupational diseases. One example is a non-ergonomic posture or body position during work (not in accordance with the principles of comfort and safety) which can trigger prolonged pain in certain parts of the body. Education from physiotherapy is very useful in helping workers understand the importance of good posture and how to reduce the risk of neck pain. Therefore, the purpose of this study was to measure the effectiveness of physiotherapy education regarding neck pain in improving the posture of workers at the UPTD Agribisnis North Pontianak. The method used in this activity was to provide health promotion counseling regarding physiotherapy education related to neck pain and posture. To measure workers' understanding, a pre-test and a post-test were conducted in the form of questions.